2008
DOI: 10.1016/j.jvs.2007.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and treatment patterns for deep venous thrombosis in hospitalized children: An increasing population at risk

Abstract: The incidence of DVT in hospitalized children is increasing. Those presenting with DVT typically have prior DVT, thrombophilia, or lower extremity disease. Our study suggests that children admitted with severe medical conditions who require a prolonged intensive care unit stay in addition to central venous access (especially via the femoral vein) should be considered candidates for DVT prophylaxis. A clinical probability scoring system alone cannot stratify patients sufficiently to forgo prophylaxis in hopes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
104
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 34 publications
(37 reference statements)
15
104
0
1
Order By: Relevance
“…13 By contrast, in a retrospective analysis of the Riley Children's Hospital experience, Sandoval and colleagues observed no consistent trend of increasing VTE risk with age, but rather a bimodal distribution of age with respect to hospital-acquired DVT, with peaks in infancy and adolescence. 14 In one of the only prospective studies of in-hospital DVT, Rohrer and colleagues observed one case of inhospital DVT in 59 at-risk children (defined by the presence of two risk factors, including surgery, trauma, immobility, stroke, cancer, sepsis, femoral venous catheterization, prior VTE, and known thrombophilia), from among 1,779 consecutive hospitalized children over a 6-month period at the University of Massachusetts Medical Center. 15 This finding emphasizes the need for further risk-stratification (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 By contrast, in a retrospective analysis of the Riley Children's Hospital experience, Sandoval and colleagues observed no consistent trend of increasing VTE risk with age, but rather a bimodal distribution of age with respect to hospital-acquired DVT, with peaks in infancy and adolescence. 14 In one of the only prospective studies of in-hospital DVT, Rohrer and colleagues observed one case of inhospital DVT in 59 at-risk children (defined by the presence of two risk factors, including surgery, trauma, immobility, stroke, cancer, sepsis, femoral venous catheterization, prior VTE, and known thrombophilia), from among 1,779 consecutive hospitalized children over a 6-month period at the University of Massachusetts Medical Center. 15 This finding emphasizes the need for further risk-stratification (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We employed a similar validation criteria approach to Sandoval and colleagues, 14 but further evaluated each admission record for the presence of signs and symptoms (unilateral limb pain/swelling) compatible with limb DVT, in order to exclude pre-hospital DVT episodes in which Table 3. Sensitivity, specificity, and pre-test probability to post-test probability changes for the risk factor model in all hospitalized patients and patients in the PICU.…”
Section: Discussionmentioning
confidence: 99%
“…Other pediatric research [8][9][10][11] described annual incidence rates of 0.07 to 0.14 per 10 000 children with rates between 4.9 and 8 per 10 000 admissions to a pediatric hospital and 24 per 10 000 admissions to a neonatal intensive care unit. More recent estimates T hromboembolic events have historically been considered an adult phenomenon.…”
mentioning
confidence: 99%
“…They often suffer complications, such as sepsis, which further heightens the risk of VTE. The reported incidence of VTE in hospitalised children has also increased because of greater recognition that thromboses are a significant risk in critically ill children (Tormene et al, 2006;Sandoval et al, 2008).…”
mentioning
confidence: 99%